The environmental study on ageing in place: the design practice compliance to accessibility legislation and standards in Malaysia for elderly home environment - Zaid, Noor Suzaini Mohamed; Yamin, Azah Abu; Yaacob, Naziaty Mohd (Foundation for Environmental Protection and Research, 2019)
Malaysia has been actively providing accessibility in the environmental built since the country signed the ‘Proclamation on the Full Participation and Equality of People with Disabilities in the Asia-Pacific Region’ in 1994. The aim of this research is to evaluate design practice compliances to accessibility legislation and design requirements in Malaysia. With regards of the increasing disability rates with age, ageing population have a significant impact on the needs of housing to be designed for future. The government regulation concerning housing design for ageing and disabled set to ensure a degree of access to their home. The role and relevance of the legislation and design requirements addressing the issue is to be practiced in the housing projects in Malaysia. On the strength of the legislations and design requirements, the analysis examines how Malaysia are practicing design solutions for housing accessibility, which encourages ageing in place. The results further reveal that such requirements was not used in the design practice and construction of housing projects in Malaysia. The outcomes are discussed considering the design requirements and concepts which can partly clarify competent design for the ageing population.